1992
DOI: 10.1128/jcm.30.11.2814-2821.1992
|View full text |Cite
|
Sign up to set email alerts
|

Infection with a plasmid-free variant Chlamydia related to Chlamydia trachomatis identified by using multiple assays for nucleic acid detection

Abstract: Clinical samples in transport media from 40 patients exhibiting pathologies potentially caused by Chlamydia trachomatis infection were analyzed for chlamydial nucleic acid, and the results were compared with those of culture. Chlamydial culture was performed by a shell vial centrifugation method with HeLa 229 host cells. Polymerase chain reaction (PCR) assays were used to detect either regions on a 7.5-kb plasmid characteristic of C. trachomatis (plasmid-PCR) or a segment of the 16S rRNA genes (rRNA-PCR). All … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
3

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 28 publications
(37 reference statements)
2
24
0
3
Order By: Relevance
“…The PCR used in this study was found to be the most sensitive method for all compartments analyzed, with detection limits comparable to those reported for other C. trachomatisspecific PCRs (1,18,23,26).…”
Section: Discussionsupporting
confidence: 78%
“…The PCR used in this study was found to be the most sensitive method for all compartments analyzed, with detection limits comparable to those reported for other C. trachomatisspecific PCRs (1,18,23,26).…”
Section: Discussionsupporting
confidence: 78%
“…Within C. trachomatis clinical isolates, the plasmid is virtually ubiquitous. There are occasional studies showing plasmid-negative clinical strains, but little is known about the epidemiology and significance of these relatively rare isolates (Peterson et al, 1990; An et al, 1992; Farencena et al, 1997). Chlamydial plasmids are nonconjugative and nonintegrative.…”
Section: The Chlamydial Plasmidmentioning
confidence: 99%
“…Using the plasmid as target DNA could theoretically increase the sensitivity compared to using a single chromosomal gene such as the omp1 gene (19). However, some studies suggest that plasmid‐free variants of C. trachomatis may on rare occasions be present in clinical samples (20), and these will not be detected if the plasmid is used as target DNA. NAATs available for detection of the cryptic plasmid in C. trachomatis in clinical specimens are the COBAS Amplicor ® Chlamydia trachomatis Test (Roche Diagnostic Systems), which is a PCR, and the Becton Dickinson BDProbeTec TM ET (Becton Dickinson) test, which uses strand displacement amplification (SDA).…”
Section: Laboratory Diagnosis Of Chlamydia Trachomatismentioning
confidence: 99%